SURVEY ON AWARENESS OF AND ATTITUDES TOWARDS INJURY PREVENTION OF THE BASKETBALL COACHES (Fiep Bulletin - online, 2011)
The aim of the study is to determine the perception of potential changes in awareness of and attitudes (knowledge and demands) towards injuries and their prevention, which was tested with the help of questionnaire based baseline in Slovak Basketball. The study is a part of the international project "Safety in Sports". We determined a level of knowledge and demands of Slovak coaches in the area of injury prevention in basketball. To gather the data a questionnaire method has been used. The data was compared to the level of knowledge and demands of the coaches in Sweden. The results make bases for evaluating expert and scientific materials, which are a part of injury prevention in basketball inventory.